2019
DOI: 10.1080/1068316x.2019.1597088
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors of delinquency that are sensitive to migration and culture

Abstract: Present evidence regarding widely used risk assessment tools suggests that such tools may have inferior predictive validity for offenders with a migration background (MB), especially from Turkey and Arab countries. Based on a thorough literature review, we investigated additional risk and protective factors via a postdictive correlational study design. We assumed that delinquency is induced by discrimination, a conflict of values, norms of honour, a disapproval of sexual self-determination, and antisemitism. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 145 publications
0
3
0
1
Order By: Relevance
“…Most measures used a contextual approach by asking about experiences of racism and discrimination in situations like at work, school, or with peers. Two studies also assessed perceived in addition to enacted stigma (Loyd et al, 2019; Schmidt et al, 2019). All studies examined racial/ethnic stigma as a predictor of outcomes, and experiencing racial/ethnic stigma was consistently associated with more externalizing symptoms (Loyd et al, 2019), risk-taking (Mendez et al, 2022), substance use (Dogan et al, 2021; Gil et al, 2004), and delinquency (Kang & Burton, 2014; Mendez et al, 2022; Schmidt et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most measures used a contextual approach by asking about experiences of racism and discrimination in situations like at work, school, or with peers. Two studies also assessed perceived in addition to enacted stigma (Loyd et al, 2019; Schmidt et al, 2019). All studies examined racial/ethnic stigma as a predictor of outcomes, and experiencing racial/ethnic stigma was consistently associated with more externalizing symptoms (Loyd et al, 2019), risk-taking (Mendez et al, 2022), substance use (Dogan et al, 2021; Gil et al, 2004), and delinquency (Kang & Burton, 2014; Mendez et al, 2022; Schmidt et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies also assessed perceived in addition to enacted stigma (Loyd et al, 2019; Schmidt et al, 2019). All studies examined racial/ethnic stigma as a predictor of outcomes, and experiencing racial/ethnic stigma was consistently associated with more externalizing symptoms (Loyd et al, 2019), risk-taking (Mendez et al, 2022), substance use (Dogan et al, 2021; Gil et al, 2004), and delinquency (Kang & Burton, 2014; Mendez et al, 2022; Schmidt et al, 2019). Only one study examined well-being outcomes and found that experiencing racial/ethnic stigma was associated with more internalizing symptoms (Loyd et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Für den Strafvollzug ist dieser Kontext in aller Regel restriktiver und selektiver als in anderen Lebenswelten. Es kommt hinzu, dass sich der Justizvollzug in den vergangenen Dekaden zunehmend zu einem multikulturellen Schmelztiegel entwickelt hat, in dem Gefangene ganz unterschiedlicher Herkunft und Kultur in Zwangsgemeinschaft zusammenleben (Schmidt et al 2016(Schmidt et al , 2019. Auch hier wird man also eine Varianz an kulturell vermittelten Vorstellungen von einem anzustrebenden Ideallebenslauf vermuten.…”
Section: Lebenszyklus Und Entwicklungsaufgabenunclassified
“…Specifically, for young male violent offenders from a Muslim cultural background in Germany, prognostic instruments did not provide a valid prediction of recidivism, in contrast to native offenders (Dahle & Schmidt, 2014). Therefore, some authors argue that to explain violent delinquency among specific groups of perpetrators, namely people with Turkish and Arabic migration or Muslim cultural backgrounds, traditional norms of honor must be considered (Dahle & Schmidt, 2014;Schmidt et al, 2017Schmidt et al, , 2019. To date, it remains to be tested whether the internalization of honor norms differs across cultural backgrounds, and whether its impact on violent behavior is independent of national origin.…”
Section: Introductionmentioning
confidence: 99%